Leading with passion and knowledge: The principal as action researcher - Thomas G Ryan (Networks: An Online Journal for Teacher Research, 2010)
Leading with Passion and Knowledge: The principal as action researcher is a book that can be placed on the same shelf as many other action research resources that are written to support, guide, and improve the practice of educators. However, this text distinguishes itself from the many books on action research by aiming to support and guide school leaders. Principals are often left to their own devices to interpret and extend texts related to education and educational research. There are few resources that lead principals through the action research process that can be critical for faculty professional development. In electing to address this issue, the author, Nancy Fichtman Dana, has chosen to open the text with a passage penned by Michael Fullan, an expert in change and leadership in education. With this endorsement, the book is instantly credible in my eyes as this foreword complements and dissects the book in an encouraging and economical manner.